Hector P. García : in relentless pursuit of justice - García, Ignacio M. (Hispanic civil rights series., 2002)
Forum, stepped into the national consciousness to fight for Longoria and his family and to inspire Mexican-American participation in party politics and against segregation in the post-World War II years.".